Comparison of efficacy combination oral terbinafine pulse-dosed and topical 8% ciclopirox olamine with terbinafine monotherapy for onychomycosis: An evidence-based case report - Bianti, Marsha; Nuary, Teffy; Widaty, Sandra (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Background: Onychomycosis is a fungal infection of the nails, which manifested as nail discoloration, thickening, and detachment from the nail bed. It is not life-threatening, however inappropriate treatment of onychomycosis might lead to complications and affect the patient’s quality of life; making the management of the disease a challenge for clinicians. Objective: Investigate the efficacy of pulse-dosed oral terbinafine combined with topical 8% ciclopirox olamine to treat onychomycosis. Methods: Literature search was performed in Pubmed and Cochrane databases using the keywords 'combination' AND 'oral terbinafine' AND 'ciclopirox' AND ‘onychomycosis treatment’ along with their synonyms and related terms. Results and Discussion: After critical appraisal, studies by Avner et al. and Jaiswal et al. found to be valid, important, and applicable to the patient. The first study found that oral terbinafine combined with topical 8% ciclopirox olamine is more effective and safe compared to terbinafine as a monotherapy (p<0.05). The second study found similar results, but without statistical significance (p>0.05). Conclusions: Oral terbinafine combined with topical 8% ciclopirox olamine is more effective than monotherapy, despite statistical irrelevance in one of the studies appraised. Further studies are needed to support the implementation of combination therapy.